Refinement for single-nanoparticle structure determination from low-quality single-shot coherent diffraction data. (2020) - Nishiyama, Toshiyuki; Niozu, Akinobu; Bostedt, Christoph; Ferguson, Ken R.; Sato, Yuhiro; Hutchison, Christopher
No abstract available